Strengthening the Biological Weapons convention in support of global peace and security - Lampalzer, Dr. Hermann Alex (One Health & Risk Management, 2025)
On 26 March 2025, the Biological Weapons Convention (BWC) celebrated its fiftieth anniversary. Over the course of the last five decades, the BWC has established itself as one of the key pillars in multilateral disarmament. The BWC builds on the foundations of the 1925 Geneva Protocol, which prohibited only the use of biological and chemical weapons in warfare. The Convention goes beyond that by comprehensively banning an entire category of weapons of mass destruction. It effectively prohibits the development, production, stockpiling, acquisition, retention and use of biological weapons against humans, animals and plants.Following its negotiation at the end of the 1960s and early 1970s in Geneva, Switzerland, the Convention was opened for signature on 10 April 1972 in London, Moscow and Washington D.C. It entered into force on 26 March 1975.